2019
DOI: 10.1002/mus.26626
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathy associated with immunoglobulin M monoclonal gammopathy: A combined sonographic and nerve conduction study

Abstract: Introduction We assessed the specific sonographic pattern of structural nerve abnormalities in immunoglobulin M (IgM) neuropathy and disease controls. Methods We enrolled 106 incident patients—32 patients with IgM neuropathy, 42 treatment‐naive patients with chronic inflammatory demyelinating polyneuropathy, and 32 patients with axonal neuropathies. All patients underwent standardized ancillary testing in addition to standardized sonography of the brachial plexus and the large arm and leg nerves bilaterally. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…DTI, diffusion tensor imaging; CSA, cross-sectional area; FA, fractional anisotropy; MD, mean diffusivity; RD, radial diffusivity; AD, axial diffusivity. 100 DOI: 10.1159/000519128 ment, including the brachial plexus and nerve root [18,19]. Goedee et al [18] showed sonographic enlargement of the brachial plexus in 26 of 32 patients with IgM neuropathy (including 21 patients with anti-MAG neuropathy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DTI, diffusion tensor imaging; CSA, cross-sectional area; FA, fractional anisotropy; MD, mean diffusivity; RD, radial diffusivity; AD, axial diffusivity. 100 DOI: 10.1159/000519128 ment, including the brachial plexus and nerve root [18,19]. Goedee et al [18] showed sonographic enlargement of the brachial plexus in 26 of 32 patients with IgM neuropathy (including 21 patients with anti-MAG neuropathy).…”
Section: Discussionmentioning
confidence: 99%
“…In an autopsy study, it has been shown that IgM deposition occurs in both distal and proximal nerves [2]. Furthermore, sonographic studies have shown widespread nerve enlargement, including the brachial plexus and nerve root [18, 19]. Goedee et al [18] showed sonographic enlargement of the brachial plexus in 26 of 32 patients with IgM neuropathy (including 21 patients with anti-MAG neuropathy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-MAG is an immune mediated demyelinating neuropathy with distally predominant symmetrical sensorimotor impairment and prolonged distal motor latencies on EDX. Despite this the ultrasound abnormalities tend to be proximal 144 and there are no reports of distal nerve enlargement. Segmental nerve enlargement has been described in cervical nerve roots, brachial plexus, and proximal nerve segments 145 with considerable inter-nerve variability.…”
Section: Generalised Peripheral Neuropathiesmentioning
confidence: 99%
“…In axonal neuropathy associated with monoclonal gammopathy of uncertain significance and multiple myeloma typically no nerve enlargement is found[ 255 , 256 ]. However, in two cases where nerve enlargement was identified in this axonal cohort, management was altered to include immunotherapy with a beneficial outcome[ 255 ], suggesting that nerve enlargement may also facilitate therapeutic decision making in these paraproteinaemic axonal neuropathies.…”
Section: Us Appearances In Peripheral Nerve Disordersmentioning
confidence: 99%